THE RELATIONSHIP BETWEEN PROTEIN INTAKE AND THE INCIDENCE OF WASTING IN INFANTS AT KLINIK HARYANTARI MEDAN - tantri, fenny ayu; Fauziah, Fauziah; Pulungan, Febry Rahmadhani; Zuhra, Fatimah; Fitry, Lely; Nababan, Tiarnida (STIKES Syedza Saintika Padang, 2025)
According to WHO (2023), improving nutritional status through the provision of nutritious food and appropriate growth and development stimulation is crucial in preventing wasting. However, in Indonesia, many mothers have not fully understood the importance of proper nutrition and stimulation. This study aims to analyze the relationship between protein intake and the incidence of wasting in infants aged 6-24 months at Klinik Haryantari Medan in 2024. This research is quantitative in nature. The research design used is cross-sectional, with a sample of 44 infants selected through purposive sampling. Data for this study were collected through questionnaires. The results showed that 34.1% of infants experienced wasting, with the majority being aged 6-12 months (43.2%) and most having normal nutritional status (65.9%). Bivariate analysis indicated that infants with low protein intake had a higher incidence of wasting (27.3%) compared to those with high protein intake (9.1%). Although the Chi-Square test showed no significant relationship between protein intake and the incidence of wasting (p=0.617), the data still suggested that low protein intake is associated with an increased risk of wasting. Klinik Haryantari is recommended to enhance nutritional education for parents regarding the importance of adequate protein intake and regular monitoring of infant nutritional status.